Effect of HOTAIR rs12826786 and rs1899663 polymorphisms on lung cancer susceptibility and clinicopathological characteristics in a turkish population: a hospital-based case-control study - Dadaş, Erdoğan; Aydın, Muhsin (Cellular and Molecular Biology, 2018)
Overexpression of Hox transcript antisense intergenic RNA (HOTAIR), a long non-coding RNA (lncRNA), is associated with tumorigenesis and multiple cancer types including lung cancer. In this study, the association between two HOTAIR single nucleotide polymorphisms (SNPs) (rs12826786 and rs1899663) on the risk and clinical characteristics of lung cancer in a Turkish population was investigated. We genotyped HOTAIR rs12826786 and rs1899663 polymorphisms in 180 Turkish people including 87 lung cancer patients (71 males and 16 females) and 93 age-matched healthy controls (67 males and 26 females) by a TaqMan real-time polymerase chain reaction method. The mean age value of the lung cancer patients and control subjects were 59.27 ± 10.55 and 61.77 ± 12.00, respectively. We found that none of the two HOTAIR polymorphisms (rs12826786 T>C, rs1899663A>C) has any significant association with the increased risk of lung cancer in any type of inheritance genetic models. However, our research indicated that carriers of Trs12826786/Crs1899663 (ht3) (P = 0.03) had an increased risk of lung cancer susceptibility.